Peran Strategis Masjid dalam Mendorong Pertumbuhan Ekonomi - Fiddini Izaturahmi; Deta Rehulina; Indah Ramadani; Wismanto Wismanto (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2025)
Mosques play a role beyond just a place of worship; they also serve as strategic community centers in driving economic growth. This study aims to explore the role of mosques in economic aspects, from providing social services, education, to community-based economic activities. By involving qualitative methods, this study collected data through interviews and observations in several mosques that are active in economic empowerment programs. The results of the study indicate that mosques can function as community centers that integrate various economic initiatives, such as skills training, providing business capital, and developing local products. In addition, mosques also play an important role in fostering social solidarity and encouraging collaboration between community members. This study is expected to provide insight for mosque managers and policy makers to maximize the role of mosques in improving the economic welfare of the community.